WORK ENGAGEMENT PADA EMPLOYEE WELL-BEING DOSEN PERGURUAN TINGGI ISLAM NEGERI - Indah Asmara Putri; Rahmi, Tuti; Febriani, Utari (Causalita, 2024)
This study aims to look at the contribution of work engagement to employee well-being for lecturers at state Islamic religious universities. This study uses a quantitative approach using survey methods. The data collection technique in this study was cluster sampling with a total of 112 lecturers at state Islamic universities in Indonesia. Methods of data analysis using simple regression with SPSS Statistics 20 for windows. Based on the results of the hypothesis test, the R square value was 0.260 and p = 0.000 (p < 0.05), so it can be concluded that work engagement contributes 26.0% to employee well-being of lecturers at state Islamic universities.